Women's perspectives on human papillomavirus self‐sampling in the context of the UK cervical screening programme. (10th February 2017) - Williams, Denitza; Davies, Myfanwy; Fiander, Alison; Farewell, Daniel; Hillier, Sharon; Brain, Kate
Abstract: Background: Testing for human papillomavirus (HPV) is being incorporated into the cervical screening programme, with the probable future introduction of HPV as a primary test and a possibility of HPV self‐sampling. In anticipation of this development, we sought to inform future policy and practice by identifying potential barriers to HPV self‐sampling. Methods: A cross‐sectional survey of 194 women aged 20‐64 years was conducted. Logistic regression analysis was used to identify determinants of self‐sampling intentions. A purposive subsample of 19 women who reported low self‐sampling intentions were interviewed. Interviews were framework‐analysed. Results: Most survey participants (N=133, 69.3%) intended to HPV self‐sample. Lower intention was associated with lower self‐efficacy (OR=24.96, P ≤.001), lower education (OR=6.06, P ≤.05) and lower perceived importance of HPV as a cause of cervical cancer (OR=2.33, P ≤.05). Interviews revealed personal and system‐related barriers. Personal barriers included a lack of knowledge about HPV self‐sampling, women's low confidence in their ability to self‐sample correctly and low confidence in the subsequent results. System‐related factors included a lack of confidence in the rationale for modifying the current cervical screening programme, and concerns about sample contamination and identity theft. Conclusions: Insights gained from this research can be used to guide further enquiry into the possibility of HPV self‐sampling and to help inform future policy and practice. Personal and system‐related barriers including low confidence in the reasons for changing current cervical screening provision need to be addressed, should HPV self‐sampling be incorporated into the cervical screening programme.